Accuracy of Conventional Radiographic Parameters in Predicting Posterior Ligamentous Complex (PLC) Rupture in Thoracolumbar Fracture Confirmed by Magnetic Resonance Imaging (MRI) - Nelly; Mirna Muis; Muh. Ilyas; Karya Triko Biakto; Andi Alfian Zainuddin (MEDULA: Jurnal Ilmiah Fakultas Kedokteran Universitas Halu Oleo, 2024)
ABSTRACT Background: Most of spinal injuries involve thoracolumbar region and are unstable. Burst fracture with posterior ligamentous complex (PLC) rupture that is not treat with surgical intervention may develop progressive kyphotic. The initial radiological examination is conventional radiographs, which can be followed by computed tomography (CT) and magnetic resonance imaging (MRI). MRI provides detail-images of soft-tissue structures so that it may provide an accurate diagnosis in predicting PLC rupture. However, the usage of MRI is still limited because of its rare availability and when patients have contraindications to MRI such as metal implants. Purpose: This study aimed to predict whether some radiographic parameters are closely related to PLC rupture, as confirmed by MRI in thoracolumbar fracture. Methods: This research is a diagnostic study using secondary data from patients who had conventional radiographic and MRI examination at Radiology Department of Dr. Wahidin Sudirohusodo which is diagnose as compression fractures and burst fractures from December 2020 until August 2022 and total of 73 samples are obtained to measure the accuracy of conventional radiographic parameters with Youden index. Results: The mean age of the sample was 41.53 years (rage 21-59 years) with more male patients than female patients and most of the fracture site is at L1. Supraspinous distance (SSD), local kyphosis (LK) and Cobb’s angle (CA) have significant p values of 0.005, 0.013 and 0.000 (respectively). Meanwhile, the anterior vertebral body compression percentage (AVBC%) and anterior edge-inferior endplate angle (AEIEA) had insignificant p values. The sensitivity, specificity and accuracy of SSD, LK and CA varied, namely 68.76%, 88.89%, 79% for SSD; 75%, 66.67%, 75.3% for LK dan 75%, 77.78, 82.2% for CA. Conclusion: From five conventional radiographic parameters that is measured, only three parameters had significant p values, which is supraspinous distance (SSD), local kyphosis (LK), and Cobb’s angle (CA) with varying sensitivity, specificity and accuracy, meanwhile anterior vertebral body compression percentage (AVBC%) and anterior edge-inferior endplate angle (AEIEA) are not correlated for predicting PLC rupture. Keywords: Cobb’s angle; local kyphosis; posterior ligamentous complex; supraspinous distanc;, thoracolumbar injury